Opportunities and challenges of implementing the legal policy of the warehouse recipe system in improving farmers welfare and food security - Abdul Halim Barkatullah; Ifrani; Muhammad Ali Amrin; Nadhira Farah Sabilla; Mutiara Caltrin Surya; Dan Muhammad Rizaldy Akmal (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: During the peak of the harvest season, falling prices are a common issue for Indonesian farmers. Farmers had exhausted their ability to store their crops due to insufficient funds and a lack of storage space. In most cases, intermediaries and loan sharks will take advantage of this situation for financial gain. This research defines the novel concept of warehouse receipts as a marketing model for agricultural commodities and examines its potential benefits for farmer income and family nutrition. Methodology: The investigation used a literature review of various books, statutes, and regulations, as well as a study of judicial decisions and advice from experts in the field. In-depth interviews were also a part of the research team’s efforts on the ground. Findings: According to the research results, the government’s SRG policy, which was developed with the farmers’ well-being in mind, had resulted in the farmers receiving legal protection, both in terms of guarantees in banks and other financial institutions and in terms of legal protection for farmers making use of the warehouse receipt system to obtain bank loans backed by guarantees. Transferring warehouse receipts and security in the form of invoices raised is possible; second, the government policy still encounters obstacles in its implementation. Several factors act as roadblocks, including: (1) Farmer’s lack of awareness regarding the availability of warehouse receipts. (2) The large number of middlemen relying on warehouse receipts leads to an overestimated inventory. (3) Internal banking regulations limit warehouse receipts as collateral because banks are wary of the potential decline in asset value. Implications/Novel Contribution: This article looks at the latest developments and discusses their benefits and drawbacks. Food supply chain management is its primary area of expertise, including inventory management, shipping, demand forecasting, and warehouse receiving. Financial institutions would rather have investments in real estate or other tangible assets whose value is stable or expected to rise over the next few years. To better the farmers’ lot, it is necessary to have federal and state governments step in so that banks feel safe lending money with warehouse receipt guarantees.